The effect of entrepreneurial orientation, social network, and resource acquisition on firm performance in Chinese SMEs: The mediating effect of resource acquisition - Xiyu Wang; Sunhae Lee; Sae Woon Park (Global Business & Finance Review (GBFR), 2020)
Purpose: The purpose of this study is to explore the impact of entrepreneurial orientation (EO), social network, and resource acquisition on firm performance in Chinese SMEs.Moreover, we analyze the impact of EO and social network on resource acquisition and further the mediating effect of resource acquisition on the relationship between EO and firm performance, and the mediating effect of resource acquisition on the relationship between social network and firm performance. Design/methodology/approach: The research is based on a survey of 204 SMEs in the Liaoning province of China, which includes entrepreneurial orientation, social network, resource acquisition, and firm performance.A structural equation model is used as the methodology. Findings: EO and social network have a significant positive impact on resource acquisition and firm performance. Resource acquisition proves to play a mediating role in the relationship between EO and firm performance, and the relationship between social network and firm performance.A higher EO can acquire more resources, and thus improve firm performance. Research limitations/implications: This research is meaningful, but it has its own limitations.First, the analysis target is limited to one area of China.If the target is expanded to other areas, different results may come out. Second, there may be measurement errors because firm performance is self-reported by the respondents.It is almost impossible that the authors gauge the accuracy and precision of these responses. The research implications are as follows: for SMEs in this region to thrive, the corporate executives should promote their entrepreneurial orientation, and strengthen their business and political ties to enhance mutual trust, and to get government support, information, loans or financing from financial institutions.These ties may also enable them to get favorable details on tax reduction Originality/value: The five-dimensional model of EO is the most prevalent in recent studies.Yet, there is not much research existent on Chinese companies.In this regard, this research using EO's five-dimensional model on Chinese SMEs may provide some contributions to the literature.
Keywords: 650; Chinese SME; Entrepreneur Orientation; Firm Performance; Resource Acquisition; SocialNetwork